105 Incidence and Predictors of Complications After Bypass Surgery for Pediatric Patients With Moyamoya Disease. (August 2015) - Lin, Yimo; Harris, Dominic; Pan, I-Wen; Luerssen, Thomas G.; Lam, Sandi
Abstract : INTRODUCTION: Moyamoya is a rare disease, and thus there have been few published studies with sufficient power for outcomes analyses of bypass surgery performed in the modern era. METHODS: This Kids Inpatient Database (KID) was queried for hospitalizations of pediatric patients with Moyamoya disease undergoing extracranial-intracranial vascular bypass surgery in the years 2003, 2006, and 2009. Type of bypass (direct vs indirect) was not distinguishable in coding. Multivariate logistic regression was conducted to identify covariates associated with in-hospital complications. RESULTS: An estimated total of 477 hospitalizations for bypass surgery were identified in the years of the study. The mean age was 9.5 years. The incidence of Down syndrome in the cohort was 7%, the incidence of sickle cell hemoglobinopathy was 12.1%, the incidence of neurofibromatosis type 1 was 5.9%, and the incidence of preexisting neurological deficit was 21%. The incidence of in-hospital complications were as follows: postoperative stroke 1%, subdural hematoma 0.4%, death 0.4%, seizures 12.2%, wound infection 1%, meningitis 0.4%, sepsis 0.4%, CSF leak 0.7%. There were no cases of cardiopulmonary collapse or deep vein thrombosis/pulmonary embolism. In a multivariate regression model controlling for demographics, hospital, and clinical factors, longer length of stay (OR, 1.12; P = .027), increased number of procedures done during hospitalization (OR, 2.2; P = .04), and the presence of 1 of 4 comorbidities (Down syndrome, NF1, sickle cell, preexisting neurological deficit) (OR, 2.3; P = .034) were significantly associated with increased risk of complications. Age, sex, race, hospital type or location, and hospital volume were not significantly associated with outcomes. CONCLUSION: Increased length of stay, increased number of procedures done in-hospital, and the presence of certain comorbidities were associated with a higher incidence of complications among pediatric patients undergoing bypass surgery for Moyamoya disease.